Multiple-objective optimization in green fuel production via catalytic deoxygenation reaction with NiO-dolomite catalyst. (15th January 2022) - Hafriz, R.S.R.M.; Arifin, N.A.; Salmiaton, A.; Yunus, R.; Taufiq-Yap, Y.H.; Saifuddin, N.M.; Shamsuddin, A.H.
Highlights: NiO-CMD catalyst has shown potential bi-functional deoxygenation catalyst due to high capacity in removing oxygen compound to produce high quality of green fuel. Synergistic effects of bi-functional NiO-CaO/MgO (acid-base) properties favored deoxyegnation pathways. NiO doped Malaysian Dolomite restricted coke formation and improved product selectivity. NiO-CMD catalyst had catalyzed simultaneous cracking- deoxygenation reaction. Abstract: This study investigates the multi-objective optimization of reaction parameters with response surface methodology (RSM) with central composite design (CCD) for the deoxygenation of waste cooking oil (WCO) over low cost-modified local carbonate mineral catalyst (NiO-Malaysian dolomite) into green fuel in the range of gasoline, kerosene and diesel. RSM was performed to study the effect of four operating parameters: temperature (390–430 °C), time (30–120 min), catalyst loading (1–10 wt%) and nitrogen flow rate (50–300 cm 3 /min). The results indicate that for maximum WCO conversion, deoxygenated oil and product yield, the optimum parameters of the deoxygenation reaction were at 410 °C, 60 min, 5.50 wt% of catalyst loading, and 175 cm 3 /min of N2 . The green fuel properties testing (density, kinematic viscosity, flash point, cloud point, pour point, sulfur, carbon residue, cetane index, oxidation stability, acid value, iodine value and calorific value) and GC–MS analysis show that the product oil meets almost all the requirements of green diesel fuel and hydrocarbon biofuel standards for fuel application while the quadratic model proposed agreed with the experimental data (95% confidence) which indicates that the RSM can adequately predict the reaction products.